Nonfunctional Overreaching Leads to Inflammation and Myostatin Upregulation in Swiss Mice - Pereira, B. C.; Pauli, J. R.; de Souza, C. T.; Ropelle, E. R.; Cintra, D. E.; Rocha, E. M.; Freitas, E. C.; Papoti, M.; da Silva, L.; Lira, F. S.; Silva, A.S. R. da (International Journal of Sports Medicine, 2014)
The aims of the this study were a) to verify whether the performance decrease induced by nonfunctional overreaching (NFOR) is linked to high concentrations of cytokines in serum, skeletal muscles and liver; b) to verify muscle myostatin adaptation to NFOR; c) to verify the effects of chronic glucose supplementation on the parameters mentioned above. Mice were divided into control (C), trained (TR), overtrained (OTR) and supplemented overtrained (OTR+S). The incremental load test (ILT) and exhaustive test (ET) were used to measure performances before and after exercise protocols. 24 h after ET, muscles and liver were removed and stored at −80°C for subsequent measurements. Total blood was collected from decapitation for subsequent determination of cytokine concentrations. Generally, OTR and OTR+S presented higher contents of IL-6, TNF-alpha, GLUT-4 and myostatin in muscle samples compared to C and TR. Glucose supplementation attenuated the high contents of IL-6, TNF-alpha and IL-15 in liver, and of IL-6 in serum. In summary, NFOR led to low-grade chronic inflammation and myostatin upregulation.
Keywords: cytokines; myostatin; nonfunctional overreaching; mice